Presence and future of plant phenotyping approaches in biostimulant research and development - De Diego, Nuria; Spíchal, Lukáš (Journal of experimental botany, 2022)
Commercial interest in biostimulants as a tool for sustainable green economics and agriculture concepts is on a steep rise, being followed by increasing demand to employ efficient scientific methods to develop new products and understand their mechanisms of action. Biostimulants represent a highly diverse group of agents derived from various natural sources. Regardless of their nutrition content and composition, they are classified by their ability to improve crop performance through enhanced nutrient use efficiency, abiotic stress tolerance, and quality of crops. Numerous reports have described modern, non-invasive sensor-based phenotyping methods in plant research. This review focuses on applying phenotyping approaches in biostimulant research and development, and maps the evolution of interaction of these two intensively growing domains. How phenotyping served to identify new biostimulants, the description of their biological activity, and the mechanism/mode of action are summarized. Special attention is dedicated to the indoor high-throughput methods using model plants suitable for biostimulant screening and developmental pipelines, and high-precision approaches used to determine biostimulant activity. The need for a complex method of testing biostimulants as multicomponent products through integrating other -omic approaches followed by advanced statistical/mathematical tools is emphasized.
Keywords: Stress, Physiological; zemědělské plodiny; Crops, Agricultural; zemědělství; výzkum; -omics; mode of action; plant biostimulants; fyziologický stres; plant breeding; Research; plant phenotyping; sensors; High-throughput screening; Agriculture; mechanism of action